Implementasi peraturan daerah kawasan tanpa rokok Kota Padang Panjang - Radian Ilmaskal; Yayi Suryo Prabandari; Trisno Agung Wibowo (Berita Kedokteran Masyarakat (BKM), 2017)
Evaluation of the implementation of the regional regulation of smoke free areas in Padang Panjang cityPurposeThis study aimed to evaluate the implementation of the regional regulation of smoke free areas (SFAs) in Padang Panjang city.MethodsThis research was a mixed method study with a sequential explanatory design. Accidental sampling was used to select the respondents. Respondents were smokers and non-smokers between 15-50 years of age living in Padang Panjang city since 2009. Informants for the qualitative data were district government authorities, community leaders and non-governmental organizations selected by purposive random sampling. Quantitative data were analyzed descriptively, while qualitative data were analyzed by content analysis. The study was conducted in April-June 2015.ResultsCompared to previous surveys in 2007, 2011 and 2013, smoking prevalence did not decrease in Padang Panjang city. Key informants suggested commitment to SFAs regulation decreased when the mayor changed, since the new mayor is a smoker. The majority of respondents (94%) supported the SFAs regulation, about 90% had not smoked in SFAs and more than 50% of smokers had not smoked in the smoking rooms such as in market (82%) and bus station (78%).ConclusionIt is suggested for the government improve promotion of SFAs regulation, raise awareness of dangers of smoking in markets, public transportation and other public spaces and improve the regulation so its qualification is everyone who wants to be a leader has to be a non smoker.